High‐Performance BeMgZnO/ZnO Heterostructure Field‐Effect Transistors. Issue 12 (27th October 2020) - Ding, Kai; Avrutin, Vitaliy; Izyumskaya, Natalia; Özgür, Ümit; Morkoç, Hadis; Šermukšnis, Emilis; Matulionis, Arvydas
Abstract : Herein, the growth and fabrication of BeMgZnO/ZnO heterostructure field‐effect transistors (HFETs) are reported on, as well as their direct current (DC) and radio frequency (RF) characterization. With a high 2D electron gas density of ≈8 × 10 12 cm −2, made possible by BeO and MgO coalloying in the barrier, typical drain currents of 0.24 A mm −1 are obtained in Zn‐polar BeMgZnO/ZnO HFETs with a Be content of 2–3% and a Mg content below 30%. Typical on/off current ratios above 10 4, transconductance values of ≈50 mS mm −1, and current‐gain cutoff frequencies f T of 5.0 GHz, the highest among ZnO‐based FETs, are achieved in devices with a gate length of 1.5 μm using Al2 O3 as the gate dielectric. An average electron velocity above 1 × 10 7 cm s −1, deduced from the bias‐dependent cutoff frequency and extraction of transit time under the gate, suggests that even with relatively long gate lengths the average electron velocity is near the theoretical limit (3.5 × 10 7 cm s −1 ) of the high peak velocity in ZnO. Abstract : BeMgZnO/ZnO heterostructures feature high 2D electron gas (2DEG) densities with relatively low Mg content achieved via strain engineering. Fabricated heterostructure field‐effect transistors (HFETs) demonstrate current‐gain cutoff frequencies of 5 GHz for 1.5 μm gate lengths. The corresponding average electron velocity above 1 × 10 7 cm s −1 inches closer to the theoretical limit of the high peak velocity in ZnO.